Exploring lysosomal defects and rescue strategies for Alzheimer's disease using human transdifferentiated neurons. (20th December 2022) - Chou, Ching‐Chieh; Vest, Ryan; Shibuya, Yohei; Prado, Miguel A; Wilson‐Grady, Joshua; Greicius, Michael D; Finley, Daniel; Wernig, Marius; Wyss‐Coray, Tony; Frydman, Judith
Abstract: Background: Aging is the critical factor of Alzheimer's disease (AD), the most common neurodegenerative disease. Among the pathological changes in the brain associated with AD, protein aggregates are the characteristic pathological hallmark that is composed of misfolded and toxic proteins. A decline in lysosomal proteolytic activity has been linked to protein aggregation and neuronal death, whereas how the lysosomes become defective and exacerbate neurodegeneration in the brain of AD patients is not well understood. Method: One of the hurdles is a lack of human neuron system to acquire deep knowledge of aging and AD. Using a powerful cell reprogramming approach, we developed a new cell model for aging and AD based on the transdifferentiation of human adult fibroblasts into cortical neurons (tNeurons) by bypassing stem‐cell stage. We leveraged cell reprogramming, quantitative proteomics, CRISPR genome editing and drug discovery techniques to achieve a better understanding of how aging and AD affect human neurons, with an emphasis on their impact on the lysosomal pathway. We further used tNeurons as a platform to identify pharmacological candidates that exert neuroprotective effect against lysosomal defects, protein aggregation and neurodegeneration in AD. Result: The transcription factor‐mediated reprogramming approach generated >85% of tNeurons as cortical glutamatergic neurons after 35‐42 days in culture. The tNeurons retained age‐related changes in epigenetic state, DNA damage and protein homeostasis (proteostasis)(Figure 1). The AD tNeurons exhibited an increased levels of Aβ42 peptides and aberrant autophagosome‐lysosome formation in the soma and neurites. Quantitative proteomics further revealed differential expression of proteins in the endosome‐lysosome and autophagy pathway between aged and AD tNeurons. We performed phenotypic and CRISPR screens to identify pharmacological candidates that ameliorate lysosomal defects and protein aggregation in aged and AD tNeurons. Conclusion: This study is anticipated to highlight that the tNeurons provide a tractable system equipped with a capacity to capture signals of human neuronal aging and neurodegenerative diseases. The outcomes provide novel insights into the role of lysosomes in the aging and neurodegenerative process, and its therapeutic implications for AD.